Applications of shear heating parameter for injection molding process optimization of AEM rubber compounds - Mattia Ramini; Silvia Agnelli; Giorgio Ramorino (eXPRESS Polymer Letters)
Shear heating phenomena during injection molding of rubber compounds greatly affect product quality but are difficult to control and replicate with laboratory tests. In this work, a very fast online process control of industrial injection molding is proposed, based on the measurement of surface temperature by infrared thermal camera of the rubber as it leaves the extruder barrel. Moreover, a new technological parameter (shear heating parameter, ηSH) is calculated from the measured temperature. A robust correlation between ηSH and viscosity from rheometric laboratory measurements was achieved for different rubber compounds. This represents an operating roadmap to support the process engineer in the improvement of process control. To show the potential of this tool, it was successfully used to optimize the injection molding of industrial production of AEM rubber compound affected by scorching and thermal degradation issues. ηSH was found to be suitable for industrial practice and able to provide accurate information about thermal history and process safety.